2002
DOI: 10.1046/j.1464-410x.2002.02796.x
|View full text |Cite
|
Sign up to set email alerts
|

Anterior prostate cancer: is it more difficult to diagnose?

Abstract: Objective To determine whether anterior prostatic tumours are adequately sampled using the Stamey sextant protocol, as a fifth of prostate cancers are anterior in distribution at radical prostatectomy. Materials and methods All tumours (62) with an anterior distribution (75% of the tumour anterior to the urethra) on radical prostatectomy whole‐mounts, and in which the number and results of the sextant biopsies were available, were extracted from a prostate cancer database. Sixty‐one posterior tumours (75% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
104
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(106 citation statements)
references
References 16 publications
2
104
0
Order By: Relevance
“…The apical region of the prostate is underrepresented in systematic transrectal biopsies due to the angulation of the probe guidance. It has been shown that localization in the anterior aspect and the apex of the prostate require significantly more biopsy sessions than posterior tumors until detection of PC [21]. In a previous MR-GB series we reported similar predominant tumor localizations, with tumors in the transitional zone in around 33% [22].…”
Section: Discussionmentioning
confidence: 58%
“…The apical region of the prostate is underrepresented in systematic transrectal biopsies due to the angulation of the probe guidance. It has been shown that localization in the anterior aspect and the apex of the prostate require significantly more biopsy sessions than posterior tumors until detection of PC [21]. In a previous MR-GB series we reported similar predominant tumor localizations, with tumors in the transitional zone in around 33% [22].…”
Section: Discussionmentioning
confidence: 58%
“…These cancers are undersampled by 10-12-core random posterior biopsies protocols and tend to be detected at more advanced stage [1,17,18]. TRUS imaging is not sensitive, whereas DCE MRI allows to identify them and to guide biopsies at earlier stage.…”
Section: Discussionmentioning
confidence: 99%
“…However, recently Sundi et al [21] reported a higher prevalence of AZ cancers in African American men with very low-risk PCa who underwent radical prostatectomy; still today no data are available regarding the incidence and clinical significance of AZ PCa diagnosed in case of initial prostate biopsy. Bott et al [8] showed that about one fifth of all index cancers were located anterior to the prostatic urethra, highlighting the need for better understanding of the clinicopathologic features of these lesions. Recently, Al-Ahmadie et al [14] in 1,312 radical prostatectomies demonstrated that 197 (15%) PCa were located in the AZ of the gland and characterized by a superimposable grading and staging in comparison with PZ PCa; Iremashvili et al [22] reported a higher rate of positive surgical margin in the presence of TZ cancer in comparison with PZ PCa in 1,141 men submitted to radical prostatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, to reduce the number of unnecessary definitive treatment, an active surveillance program has been introduced in clinical practice, but still today the risk of understaging and/or undergrading PCa is equal to 30% [3,4], and certain criteria to assess the aggressiveness of PCa in the early stage are still missing. Although magnetic resonance imaging [5] and targeted magnetic resonance imaging/ultrasound fusion-guided biopsy [6,7] have improved extended and saturation biopsy schemes' accuracy in detecting significant PCa, the rate of repeat prostate biopsy is equal to 30-40%, with an high percentage of cancer detected in the anterior zone (AZ) of the gland (about 20% of cases) [5,8]. …”
Section: Introductionmentioning
confidence: 99%